PENERAPAN EVIDENCE BASED NURSING TERAPI DZIKIR DAN TERAPI BENSON TERHADAP PENINGKATAN KUALITAS TIDUR PASIEN ICU DI RSUD KHIDMAT SEHAT AFIAT KOTA DEPOK - Putri Irayani (2023)
The Intensive Care Unit (ICU) room is an environment that is considered a place that can cause anxiety and even threaten patients. Patients who are in the ICU must be able to adapt to a new environment that can make them feel uncomfortable so that it affects the quality of sleep for patients in the Intensive Care Unit room. One of the non-pharmacological therapies that can be used to improve sleep quality is dhikr therapy in combination with benson therapy. The application of this therapy aims to determine the effectiveness of dhikr therapy and benson therapy on sleep quality in patients in the ICU. Measurement of sleep quality in this study used the Pittsburgh Sleep Quality Index (PSQI) and a digital sleep tracking application. The results of the case study showed that there was a significant increase in the quality of sleep in patients after being given dhikr therapy intervention and benson therapy for five days of intervention. It is hoped that dhikr therapy and benson therapy can be used as non-pharmacological management to improve sleep quality in patients in the ICU.